1991
DOI: 10.2165/00003495-199142050-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Interferon-α in Virus Infections

Abstract: The interferons (IFN) act too slowly to arrest acute viral infections, but interferon-alpha (IFN alpha) preparations have proved useful in some chronic infections and will clearly be used increasingly in these in the future. In the preparations derived from human leucocytes or cultured B lymphoblastoid cells, which are in routine clinical use, mixtures of a number of distinct subtypes of human IFN alpha have been identified. There are also 3 slightly different versions of the same single subtype, IFN alpha-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 114 publications
0
34
0
Order By: Relevance
“…Today, IFN-␣ is established as an essential component of hepatitis B and C treatment regimens (9,17,31). Even though clinical studies demonstrated that intranansal IFN-␣ treatment can also prevent rhinovirus infection and spread (6,14,15), side effects such as irritation of the nasal mucosa and occasional nose bleeding after long-time and repeated administration prevented further in-depth evaluation of the potential therapeutic use of IFN-␣ to combat respiratory diseases such as influenza. The current interest in drugs against influenza is fueled by the threat that circulating avian H5N1 viruses or another subtype may adapt to humans and cause a devastating pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, IFN-␣ is established as an essential component of hepatitis B and C treatment regimens (9,17,31). Even though clinical studies demonstrated that intranansal IFN-␣ treatment can also prevent rhinovirus infection and spread (6,14,15), side effects such as irritation of the nasal mucosa and occasional nose bleeding after long-time and repeated administration prevented further in-depth evaluation of the potential therapeutic use of IFN-␣ to combat respiratory diseases such as influenza. The current interest in drugs against influenza is fueled by the threat that circulating avian H5N1 viruses or another subtype may adapt to humans and cause a devastating pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The human MxA protein also inhibits the replication of influenza viruses (30,53). In spite of promising initial clinical studies with IFN-␣ for the treatment of respiratory diseases, side effects such as irritation of the nasal mucosa and occasional nose bleeding have prevented the in-depth evaluation of IFN-␣ as a treatment for these diseases (6,15,19,25). If intranasally applied IFN were effective against influenza A viruses, the benefit would in many cases outweigh the reported mild side effects of the treatment.…”
mentioning
confidence: 99%
“…Initially identified as antiviral proteins, IFNs-␣/␤ are now known to be pleiotropic and plurifunctional molecules with antiproliferative and immune-regulatory properties (32,41), which has led to their widespread therapeutic use in patients with certain viral infections (16), various cancers (21), and autoimmune disorders (11,38). The binding of IFNs to their common receptor, named the IFN-␣/␤ receptor (IFNAR), activates a signaling cascade involving the Janus kinase /signal transducer and activator of transcription (STAT) pathway (41).…”
mentioning
confidence: 99%
“…Such treatments with these limited subtypes overlook the possible therapeutic potential of the other natural IFN subtypes with divergent biological functions. Furthermore, although most IFNs are biologically active in the picomolar range, conventional IFN treatment uses systemic administration of extraordinary high doses, often associated with severe side effects including neurological toxicity limiting treatment efficacy [7,33,34]. Alternative treatment regimes using low dose IFN application, directed to the mucosal immune system, have shown improved clinical efficacy against virus infection in an experimental setting [34][35][36][37].…”
Section: Current Ifn Treatment For Virus Infectionsmentioning
confidence: 99%